Moral Disengagement and School Aggression at the Elementary SchoolLevel: The Mediating Role of Shame - Ochoa Arreola, José Alan; Tánori Quintana, Jesús; Flores Partida, Cesar Alan; Vera Noriega, José Ángel; Montoya Aguilar, José Luis (Emerging Trends in Education, 2026)
This study analyzed the relationship between moral disengagement and aggressive behaviors in elementary schoolstudents, considering the mediating role of shame and the moderating effect of sex. A cross-sectional design witha quantitative and explanatory scope was employed. The sample consisted of 562 students from fifth and sixthgrade attending public schools in Sonora, Mexico (56.8% male, 43.2% female; M = 10.70 years, SD = 0.65).Validated scales measuring aggression, moral disengagement, and shame were administered. Analyses includeddescriptive statistics, Pearson correlations, Student’s t-tests, and a moderated mediation model using PROCESSin JASP. Results revealed positive and significant associations among moral disengagement, shame, andaggressive behaviors. Moral disengagement was directly related to aggression (β = .24), and shame partiallymediated this relationship (β = .03). Significant differences by sex were observed in aggression and moraldisengagement, although the interaction between moral disengagement and sex was not significant. In conclusion,moral disengagement and shame are key factors in understanding school aggression in elementary education.These findings highlight the importance of designing preventive interventions that integrate both cognitive andemotional dimensions, while also considering differences between boys and girls.
Keywords: aggression; elementary education; school mediation; gender differences